Ophiostomatoid fungi associated with pine bark beetles and infested pines in south-eastern Australia, including Graphilbum ipis-grandicollis sp. nov. - Conrad Trollip; Angus J. Carnegie; Quang Dinh; Jatinder Kaur; David Smith; Ross Mann; Brendan Rodoni; Jacqueline Edwards (IMA Fungus)
Abstract The ophiostomatoid fungi are an assemblage of ascomycetes which are arguably best-known for their associations with bark and ambrosia beetles (Curculonidae) and blue stain (sap stain) of many economically important tree species. These fungi are considered a significant threat to coniferous forests, which has resulted in numerous studies characterising the diversity of bark beetles and their ophiostomatoid associates globally. The diversity of ophiostomatoid fungi present in Australian pine plantations, however, remains largely undetermined. The aims of this study were therefore to reconsider the diversity of ophiostomatoid fungi associated with Pinus in Australia, and to establish the baseline of expected taxa found within these plantation ecosystems. To achieve this, we reviewed Australian plant pathogen reference collections, and analysed samples collected during forest health surveillance programs from the major pine growing regions in south-eastern Australia. In total, 135 ophiostomatoid isolates (15 from reference collections and 120 collected during the current study) were assessed using morphological identification and ITS screening which putatively distinguished 15 taxonomic groups. Whole genome sequencing (WGS) of representative isolates from each taxon was performed to obtain high-quality sequence data for multi-locus phylogenetic analysis. Our results revealed a greater than expected diversity, expanding the status of ophiostomatoid fungi associated with Pinus in Australia to include 14 species from six genera in the Ophiostomatales and a single species residing in the Microascales. While most of these were already known to science, our study includes seven first records for Australia and the description of one new species, Graphilbum ipis-grandicollis sp. nov.. This study also provides an early example of whole genome sequencing (WGS) approaches replacing traditional PCR-based methods for taxonomic surveys. This not only allowed for robust multi-locus sequence extraction during taxonomic assessment, but also permitted the rapid establishment of a curated genomic database for ophiostomatoid fungi which will continue to aid in the development of improved diagnostic resources and capabilities for Australian biosecurity.